The Icon, a Hexadic Analysis - Cristina Stratulat (Anastasis: Research in Medieval Culture and Art)
The present paper brings forward an analysis of the Orthodox icon, made by deploying the model of semi-logical hexade which describes the situation of creative communication. Starting with the presentation of the socio-cultural context in which the icon appears and continuing with the other parameters of the hexade – the purpose which justifies the activation of the creative act, whom is this icon addressed, who created it, what psychological mechanisms have concurred to its birth and which is the result of this creative process – our focus has been the defining and description of what the icon is.